A new HLA‐DPB1 allele, HLA‐DPB1*142:01, identified in a Peruvian organ donor. Issue 3 (19th August 2013) - Balas, A.; Planelles, D.; Puig, N.; Montoro, J. A.; Vicario, J. L.
Abstract : The new HLA‐DPB1*142:01 allele differs from DPB1*26:01:02 and DPB1*56:01 at codons 65 (I65>L65) and 35 (F35>Y35), respectively.